Study of the biological risks of workers in the activity of waste separation in recycling cooperatives (Research, Society and Development, 2023)
Due to the failure of biosecurity protocols in recycling cooperatives, waste separators are exposed to biological agents, such as viruses, fungi and bacteria, making them more susceptible to infections by these agents. This study aimed to study the biological risk to which cooperative members are exposed in the activity of sorting/separating recyclable waste, evaluating the use of personal protective equipment and the occurrence of accidents and the practice of hand hygiene. For this, a quantitative descriptive study was carried out in the State of Alagoas, in the COOPREL and COOPLUM Waste Recycling Cooperatives. The occurrence of microorganisms from the handling of waste was investigated by collecting material from the hands of the cooperative members, with the aid of a swab, before and after the usual cleaning process, followed by the guided one. The collected material was transported and analyzed for the presence of aerobic and anaerobic bacteria, molds and yeasts. After cultivation and microbiological analysis, the presence of microorganisms from the Enterobacreriaceae family, molds and yeasts was verified. However, the collection performed after the oriented hygiene showed a significant reduction in the number of bacteria by 88%; in relation to the initial sample of the collection before or after the usual cleaning. Regarding the presence of molds and yeasts, a reduction of 37.50% was observed. Therefore, this study identified that 54% of the cooperative members suffered accidents with sharps in the last twelve months, and identified bacteria of the Enterobacteriaceae family in the hands of the cooperative members (56.41%), reflecting, in addition to the biological risk, the exacerbation of the social risk represented by the precarious working conditions.